Planar and Non Planar Construction of ï§- Uniquely Colorable Graph - Elakkiya, A.; Yamuna, M. (International Journal of Engineering and Technology, 2018)
A uniquely colorable graph G whose chromatic partition contains atleast one g - set is termed as a g - uniquely colorable graph. In this paper, we provide necessary and sufficient condition for and G* to be g - uniquely colorable whenever GÂ  g- uniquely colorable and also provide constructive characterization to show that whenever G is g- uniquely colorable such that |P | Â³ 2, G can be both planarand non planar.Â